2009
DOI: 10.1177/1358863x08098227
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model for amputation in critical lower limb ischemia

Abstract: In a (negative) multicenter randomized trial on management for inoperable critical lower limb ischemia, comparing spinal cord stimulation and best medical treatment, a number of pre-defined factors were analyzed for prognostic value. We included a radiological arterial disease score, modified from the SVS/ISCVS runoff score. The purpose of this analysis was to evaluate clinical factors and commonly used circulatory measurements for prognostic modeling in patients with critical lower limb ischemia. We determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Meta-analysis of these trials demonstrated that patients with tissue loss have a higher amputation rate than those with rest pain (Hazard Ratio 8.650, p = 0.0513). This is further supported by a separate analysis of patients in a spinal cord trial in which those with tissue loss demonstrated a higher amputation risk (HR 2.38, p = 0.018) [ 16 ].…”
Section: Discussionmentioning
confidence: 82%
“…Meta-analysis of these trials demonstrated that patients with tissue loss have a higher amputation rate than those with rest pain (Hazard Ratio 8.650, p = 0.0513). This is further supported by a separate analysis of patients in a spinal cord trial in which those with tissue loss demonstrated a higher amputation risk (HR 2.38, p = 0.018) [ 16 ].…”
Section: Discussionmentioning
confidence: 82%
“…Table 3 presents the segments with their anatomic borders. Several other groups have developed complex lesion and anatomy assessment below the knee and in the pedal arch, including the angiosome concept (27,28). The PARC group recommends continued research and data capture in relevant patients with distal disease to help inform future efforts.…”
Section: Parc Definitionsmentioning
confidence: 99%
“…In patients with nonreconstructible CLI, a higher radiological arterial disease score is significantly associated with amputation risk. 23 Al-Khoury et al 15 reported outcome following isolated CFE and suggested that patients with The TransAtlantic InterSociety Consensus (TASC) C and D SFA lesions are at increased risk of developing recurrent symptoms; however, this study included patients with both intermittent claudication and CLI. Secondly, they grouped patients based on number of patent arteries when analyzing runoff, whereas we have evaluated the level of disease in each runoff artery and based on the SVS score.…”
Section: Discussionmentioning
confidence: 98%